Examination of Quaternary Ammonium Compound Resistance in Proteus mirabilis Isolated from Cooked Meat Products in China - Jiang, Xiaobing; Yu, Tao; Liu, Lei; Li, Yi; Zhang, Kun; Wang, Hailei; Shi, Lei (Frontiers in Microbiology, 2017)
The aim of this study was to examine the presence of genes responsible for resistance to quaternary ammonium compounds (QACs) and the association of qac genes with class 1 integrons in Proteus mirabilis isolated from cooked meat products. A total of 52 P. mirabilis isolates (29.2%) were detected from 178 samples, and their minimum inhibitory concentrations (MICs) of benzalkonium chloride (BC) ranged from 4 to >32 μg/mL. The isolates with BC MICs of 24 μg/mL were observed most frequently. PCR assays indicated that mdfA, ydgE/ydgF, qacE, qacEΔ1, emrE, sugE(c) and sugE(p) were commonly present (32.7%-100%) in these isolates, but qacH was less prevalent (3.8%). Five groups of resistance gene cassettes were identified in 10 intI1-positive isolates. An unusual gene cassette array dfrA32-ereA-aadA2 was found in one foodborne isolate of P. mirabilis. Two isolates harbored qacH- and sul3- associated non-classic integrons: aadA2-cmlA1-aadA1-qacH-IS440-sul3 and a new arrangement dfrA32-ereA1-aadA2-cmlA1-aadA1-qacH-IS440-sul3, which is first reported in P. mirabilis. Non-classic class 1 integrons were located on conjugative plasmids of 100 kb in two tested isolates. Our data showed that the QAC resistance genes were commonly present among P. mirabilis isolates from cooked meats and qacH was associated with non-classic class 1 integrons. The creation of transconjugants demonstrated that qacH-associated non-classic class 1 integrons were located on conjugative plasmids and therefore could facilitate the co-dissemination of disinfectant and antimicrobial resistance genes among bacteria, an increasing area of concern.